Analisis Korelasi Kemampuan Berpikir Kritis Siswa Dalam Menyelesaikan Soal Numerasi di Kelas VIII SMPS Prayatna Medan - Nainggolan, Helni Wirani; Aprina, Laura; Sitorus, Mika; Sembiring, Ramizulna Br; Hutasoit, Tibelida (Jurnal Media Informatika, 2024)
This study aims to analyze students' critical thinking skills in solving numeracy-based problems. This research is a qualitative research type by taking students of grade VIII of SMPS Prayatna Medan as research subjects. The data used in this study were obtained by giving tests to students. The test sheet given contains numeracy-based problems. Based on the results of the study, it was found that the critical thinking skills of students at SMPS Prayatna Medan in solving numerical problems were still at a low level. Although the numeracy problems given have been designed to challenge critical thinking, the results obtained by students have not been maximized. This indicates a link between critical thinking skills and students' success in understanding and solving complex numeracy problems